Mielografia e tomografia computadorizada de afecções compressivas da medula espinhal em cães - Avante, Michelle Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Spinal cord injuries often occur in small animals due to exogenous or endogenous causes. Spinal cord injury is classified into extradural, intradural-extramedullary and intramedullary. This study aims to determine the lesions involving the spinal cord and its findings and different frequencies to myelography. At the same time, another study with six patients with inconclusive examinations to myelography underwent computed tomography contrasting and their findings were compared with myelography. In this study were reassessed 154 cases of dogs with neurological clinical suspicion surrounding the spinal cord, which underwent conventional radiographs and myelography with nonionic iodinated compound in the period 2008 to 2012. The imaging studies were developed in Sector Diagnostic Imaging Veterinary Hospital Governador Laudo Natel of the Faculdade de Ciências Agrárias e Veterinárias Jaboticabal - Unesp. Among the different breeds of dogs, the Teckel were the most affected with the presentation of 58 patients (38%). The age group most frequent was 5-8 years, totaling 67 dogs (43.5%). The cervical column was the most frequent segment of the lesions found in 88 lesions (44%). The most common location of lesions was extradural corresponding to lesions of the total analyzed 191 (95.5%) and nine lesions were intradural extramedullary (4.5%). Extradural lesions of 175 (91.6%) were degenerative intervertebral disc protrusion / extrusion. Aside from the 154 cases in the first half of 2013, in six other patients were performed sequentially myelography and computed tomography. In these cases the lesions were in the neck: three cases (50%), two in the lower back (33%) and one thoracolumbar (17%). All lesions were extradural three cases of disc extrusion (50%), two protrusion (33.3%) and one for cancer/osteomyelitis (16.7%). The myelography permits, in most cases lead to a definitive diagnosis in patients with spinal cord compression injury. Computed ...

Lesões da medula espinhal ocorrem frequentemente em pequenos animais em razão de causas exógenas ou endógenas. A lesão medular é classificada em extradural, intradural-extramedular e intramedular. Este estudo tem como objetivo determinar as lesões que envolvem a medula espinhal e seus diferentes achados e frequências à mielografia. Paralelamente, um outro estudo com seis pacientes com exames inconclusivos à mielografia foram submetidos à tomografia computadorizada contrastada e seus achados foram confrontados com a mielografia. Neste estudo foram reavaliados 154 casos de cães com suspeita clínica neurológica envolvendo a medula espinhal, os quais foram submetidos a exames radiográficos convencionais e à mielografia com composto iodado não iônico no período de 2008 a 2012. Os exames imaginológicos foram desenvolvidos no Setor Diagnóstico por Imagem do Hospital Veterinário Governador Laudo Natel da Faculdade de Ciências Agrária e Veterinária de Jaboticabal - Unesp. Entre as diferentes raças de cães, a Teckel foi mais acometida com a apresentação de 58 pacientes (38%). A faixa etária de maior ocorrência foi de cinco a oito anos, totalizando 67 cães (43,5%). A coluna cervical foi o segmento de maior ocorrência das lesões encontradas com 88 lesões (44%). A localização mais frequente das lesões foi extradural, correspondente a 191 lesões do total analisado (95,5%) e nove lesões foram intradurais-extramedulares (4,5%). Das lesões extradurais, 175 (91,6%) foram de origem degenerativa do disco intervertebral, protrusão/extrusão. Com exceção dos 154 casos, no primeiro semestre de 2013, em seis outros pacientes foram realizados, sequencialmente, mielografias e tomografia computadorizada. Nestes casos as lesões foram em região cervical: três casos (50%), dois na região lombar (33%) e um toracolombar (17%). Todas as lesões foram extradurais, três casos de extrusão do disco (50%), dois de...
Keywords: Cão; Medula espinhal; Mielografia; Tomografia; Ferimentos e lesões; Spinal cord